TECENDO AS TEIAS DO ABANDONO: Além das percepções das mães de bebês prematuros - Fernandes, Rosângela Torquato (2009)
Descriptive qualitative study aiming at understanding the social representations of mothers of premature babies when abandoning them. We presumed, in the present study, that preterm babies are more likely to be discarded due to the mothers early estrangement, prolonged hospital staying, and because of the increased rates of comorbidity. The research was undertaken in the neonatology sector, Newborn Intensive Care Unit (NICU)), Mother Baby Unit (UMB) and ambulatory segment of the University Hospital of the Federal University of Maranhão Infant Maternal Unit. The project was carried out after approval by the Research Ethics Board. Mother of preterm baby being treated at the NICU was the inclusion criterion. Mothers of infants with malformation and those whose babies had suffered anoxia were excluded from the study. Our sampling followed the qualitative methodology criteria of field saturation with 12 participating mothers. The data were collected in the period of September 2007 and March 2008, and for such, instrument triangulation was used: reading of social cards from newborn medical records, semi-structured interviews with the mothers, and observation at the moment of the interviews, and focus group. The data management were based on basics of the content analysis method in the thematic analysis modality. Among the results, it is highlighted that the representation of mothers on the subject undergoes changes consistent with the period of the baby s hospitalization. It is not possible to talk about the subject initially, that only happens when in group in the segment ambulatory. They bear the necessity of being motherly in order to learn to care for their infant. The mother being abandoned by her mate and her family, as well as economical status, are risk factors for a mother abandoning her infant. In conclusion, we draw attention to the need of a support network made up by professionals, mates, and the family in such a maternal fragility moment, where that protection starts during prenatal care lasting up to the puerperal period. With the protection those mothers may overcome the fear, the guilt and empower themselves in the baby s care contributing to not neglecting their care.